NASAL CARRIAGE OF STAPHYLOCOCCUS AUREUS AMONG HEALTHCARE WORKERS IN KHARKIV MEDICAL FACILITIES - Kalinichenko, S.V.; Dubinina, N.V.; Kovalenko О.І.; Minukhin, V.V.; Bilozerskyi V.І.; Isaenko О.Yu.; Antusheva, T.I. (World of Medicine and Biology, 2025)
The study was devoted to the problem of Staphylococcus aureus carriage among employees of medical institutions in Kharkiv in order to objectively investigate bacterial carriage as one of the causes of the spread of nosocomial infections. 309 employees of medical institutions in Kharkiv were examined. It was found that 31.7 % of those examined were carriers of S. aureus. Among all the isolated S. aureus isolates, 40 % were resistant to methicillin, and 3.5 % were resistant to vancomycin. To determine the routes of intrahospital spread of S. aureus and identify possible sources of infection, we performed phage typing on the isolated S. aureus isolates. It was found that in the surgical and somatic departments, S. aureus isolates of phage types 2 and 3 prevailed. This indicates their epidemiological significance. The results of our study on Staphylococcus aureus carriage among medical personnel in Kharkiv hospitals emphasize the need to establish systematic surveillance and preventive strategies aimed at reducing the risk of healthcare-associated infections.